2013
DOI: 10.1080/02640414.2013.843013
|View full text |Cite
|
Sign up to set email alerts
|

Measuring kinematic changes of the foot using a gyro sensor during intense running

Abstract: Gyro sensor has been used to measure foot pronation during running with reliable results in previous studies, and the signals were not affected by the vibration of heel strikes. The purpose of this study was to observe the kinematic changes of the foot during intense running using a 3-axis gyro sensor. Fifteen male participants (average age: 24.5 ± 1.7 years; mean height: 174.1 ± 3.3 cm; mean body weight: 71.0 ± 5.5 kg) were recruited in this study. Foot kinematic changes were observed in 30-min intense runnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 36 publications
1
15
1
Order By: Relevance
“…In this context, studies have reported that high eversion velocities could be associated with medial tibial stress syndrome [1][2][3]. Aside from investigating injuries, previous studies examined the influence of footwear construction or foot orthoses [1,[4][5][6][7], exhaustion [8], and running pace [9] on maximum eversion velocity and the time until it occurs.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In this context, studies have reported that high eversion velocities could be associated with medial tibial stress syndrome [1][2][3]. Aside from investigating injuries, previous studies examined the influence of footwear construction or foot orthoses [1,[4][5][6][7], exhaustion [8], and running pace [9] on maximum eversion velocity and the time until it occurs.…”
Section: Introductionmentioning
confidence: 99%
“…When examining the agreement of the maximum angular velocity of the shoe in the frontal plane (eversion velocity), they found moderate [8], acceptable [10], and good [14] agreement between the systems. Investigated running speeds were in a narrow range between 3.2 ± 0.4 and 4.0 ± 0.2 m/s.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations